2022
DOI: 10.2217/nnm-2022-0151
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Encoding Mirna-200C Delivered by Caco 3 -Based Nanoparticles Enhances Rat Alveolar Bone Formation

Abstract: Aim: miRNAs have been shown to improve the restoration of craniofacial bone defects. This work aimed to enhance transfection efficiency and miR-200c-induced bone formation in alveolar bone defects via plasmid DNA encoding miR-200c delivery from CaCO3 nanoparticles. Materials & methods: The CaCO3/ miR-200c delivery system was evaluated in vitro (microscopy, transfection efficiency, biocompatibility) and miR-200c-induced in vivo alveolar bone formation was assessed via micro-computed tomography and histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…Figures 5C and D Previous studies have reported that CaCO3-based nanoparticles can effectively improve transfection efficiencies of pDNA encoding miR-200c into human preosteoblasts (Remy et al 2022). Local application of collagen sponges incorporating CaCO3/pDNA miR-200c complexes effectively enhances bone formation in alveolar bone defects (Remy et al 2022). In the present studies, it is confirmed that the system of CaCO3 with PS co-precipitation nanoparticles effectively improves transfection efficiencies of pDNA encoding miR-200c into OSCC cells.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Figures 5C and D Previous studies have reported that CaCO3-based nanoparticles can effectively improve transfection efficiencies of pDNA encoding miR-200c into human preosteoblasts (Remy et al 2022). Local application of collagen sponges incorporating CaCO3/pDNA miR-200c complexes effectively enhances bone formation in alveolar bone defects (Remy et al 2022). In the present studies, it is confirmed that the system of CaCO3 with PS co-precipitation nanoparticles effectively improves transfection efficiencies of pDNA encoding miR-200c into OSCC cells.…”
Section: Resultssupporting
confidence: 81%
“…Quantitatively, GFP expression measured qRT-PCR was significantly higher in tumor tissue with miR-200c treatment than that of untreated controls (Figure 5B). Figures 5C and D Previous studies have reported that CaCO3-based nanoparticles can effectively improve transfection efficiencies of pDNA encoding miR-200c into human preosteoblasts (Remy et al 2022). Local application of collagen sponges incorporating CaCO3/pDNA miR-200c complexes effectively enhances bone formation in alveolar bone defects (Remy et al 2022).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Notably, protamine sulfate (PS), a clinically used antidote for heparin-induced anticoagulation, has been reported to substantially improve the transfection efficiency of CaCO 3 -mediated plasmid DNA (pDNA) into cells (Wang et al 2014; He et al 2018). Our previous studies have demonstrated that pDNA miR-200c delivered by CaCO 3 effectively improves transfection efficiency and alveolar bone formation (Remy et al 2022). CaCO 3 -based nanoparticles have also been developed for cancer therapy (Chen et al 2016; Poojari et al 2016).…”
Section: Introductionmentioning
confidence: 99%